Architects for Future goes Hochschule (EAAE Annual Conference Proceedings, 2024)
Architects for Future have articulated 10 demands for a transition of the building  and construction sector to sustainable practices. This shift must be embedded and construction sector. This shift must be embedded in educational programs, and we need to establish new networks and teaching initiatives.Together for the the building transition, the “Bauwende”! Since 2019 Architects for Future has been the leading voice in the movement for the Bauwende in Germany. More and more people are joining our cause, which has now become international. In 2023 we were invited to hold a visiting which has now become international. In 2023, we were invited to hold a visiting professorship in “Architecture for Future” at TU Berlin, where we integrated Bauwende in the architectural curriculum. In 2024, we launched a new network of professors who are committed to incorporating the Bauwende into their courses. We also started a new hybrid lecture and dialogue series, with 13 universities participating and 22 experts providing insights on the 10 demands of Architects for Future. Each week, we reached over 750 students. We intentionally sought to introduce the topics of the Bauwende and the climate movement into education to raise students’ awareness and knowledge, while also encouraging political engagement to some extent. Architecture is far more political than many realize, but these connections have yet to be adequately addressed in academic programs.